STUDI PENGELOLAAN KEUANGAN UMKM DI DACRON HOUSE PRINGAPUS KABUPATEN SEMARANG - Nitorman Zalukhu; Andhi Supriyadi (Media Bina Ilmiah, 2025)
To provide a positive impact on small and medium enterprises (SMEs), financial management must be implemented transparently and accurately. They face problems with financial organization and human asset skills. This study aims to determine the financial management carried out at Dacron House Pringapus, Semarang Regency, as well as the supporting and inhibiting factors that contribute to the financial management. This study is a field research study with a case study approach, namely collecting data from observations, interviews, and documentation related to the focus of the study. By categorizing, confirming, and making conclusions, the data was examined for validity. The triangulation technique and the triangulation method technique were the data validity tests employed in this investigation. This study shows that: (1) The financial management of the Dacron House Pringapus business in Semarang Regency has not been fully carried out because financial planning, recording, and supervision have been carried out properly, but financial reporting is not carried out comprehensively every month. (2) Factors that support the management of business finances at Dacron House Pringapus, Semarang Regency are the awareness of MSME actors and their use. Ignorance, separation between business and personal money, and lack of financial recording skills are some of the obstacles to managing their finances